BUSINESS ANALYSIS OF FISH CRACKERS (ATOM EMY CRACKERS) IN MALANG VILLAGE MEETING GUNUNG KIJANG SUBDISTRICT, BINTAN REGENCY, RIAU ISLAND PROVINCE - Suci Nurul Ulfia; Lamun Bathara; Hazmi Arief (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT    This research is about the analysis of Tenggiri fish cracker (Emy Atom Cracker) business, aims to find out the acceptance, profit and analyze business feasibility by using business profitability. This research was conducted in April 2018 in Malang Village Meeting of Gunung Kijang District, Bintan Regency, Riau Islands Province. The research method uses a case study method, the respondents taken in this study are Emy Atom Cracker business owners. The results of this study show a total investment of IDR.265,119,200, the total production cost of IDR.44,853,120, with a fixed cost of IDR.1.439.920 and a percentage of income of 3,2% and a fixed cost of IDR.43,413,200 and the percentage of income of 96,7% profit of 1 month emy atom cracker business of IDR.34,446,900.               Analysis of Revenue Cost Ratio (RCR) business profitability in Emy Atom Cracker business of 1,7 in accordance with RCR Criteria shows that the Emy Atom Cracker business is feasible to be developed, Payback Period Of Capital (PPC) in Emy Atom Cracker business is 7,6 which means it takes time for 7 year 6 month for the return of investment by Emy Atom Cracker entrepreneurs, the Profit to Investment Ratio (ROI) in the Emy Atom Cracker business of 13% as with the ROI criteria which means this effort is successful to be developed. Keywords: Crackers, Mackerel Fish, Business Analysis